Digital Intervention in National Political Systems in the Conditions of Contemporary Information Society - Volodenkov, Sergey V. (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The article analyzes the phenomenon of digital interference with national political systems in the conditions of the modern information society and the evolution of the Internet as a space of political communications. It is shown that digital intervention is relevant but at the same time a complex multidimensional phenomenon of contemporary politics. In many respects, the potential of the digital interference phenomenon is closely related to the substantive and functional features of the functioning and transformation of the contemporary Internet, which has been actively used when changing political regimes in many countries. The initiatives of countries to form the sovereign national segments of the Internet space are, on the one hand, an attempt to protect their political systems from external influence and invasion, to ensure their own political stability, and on the other hand, they pose risks to the democratic potential of the Internet. The article substantiates the thesis that the phenomenon of interference with elections in actual practice often becomes not so much an objective process as an instrument of information warfare, mass political propaganda and discredit of political opponents, a manipulative tool that can be actively used not only by authoritarian regimes with a low level of democratic development. It is noted that differences in understanding and defining the essence of the Internet by various countries give rise to a significant potential for political conflicts on a global scale. This leads the author to conclude that it is necessary to form institutions that are able to prevent and regu- late information conflicts in the Internet space, as well as reduce global political risks (including risks associated with potential interference in the electoral process of sovereign states), forming a collective responsibility in the functioning of the global Internet.

Artykuł analizuje zjawisko ingerencji cyfrowej w krajowe systemy polityczne w warunkach współczesnego społeczeństwa informacyjnego oraz ewolucję Internetu jako przestrzeni komunikacji politycznej. Wykazano, że interwencja cyfrowa to istotne i jednocześnie złożone, wielowymiarowe zjawisko współczesnej polityki. Pod wieloma względami potencjał zjawiska zakłóceń cyfrowych jest ściśle związany z merytorycznymi i funkcjonalnymi cechami działania i transformacji współczesnego Internetu, który jest aktywnie wykorzystywany przy zmianie ustrojów politycznych w wielu krajach. Inicjatywy krajów zmierzające do utworzenia suwerennych krajowych segmentów przestrzeni internetowej są – z jednej strony – podejmowaną w celu zapewnienia sobie stabilności politycznej próbą ochrony swoich systemów politycznych przed wpływami zewnętrznymi i inwazją, a z drugiej strony, stanowią ryzyko dla demokratycznego potencjału Internetu. Artykuł uzasadnia tezę, że w praktyce zjawisko ingerencji w wybory często staje się nie tyle obiektywnym procesem, co narzędziem wojny informacyjnej, masowej propagandy politycznej i dyskredytacji przeciwników politycznych oraz narzędziem manipulacji, które może być aktywnie wykorzystywane nie tylko przez reżimy autorytarne o niskim poziomie rozwoju demokratycznego. Podkreślono, że różnice w rozumieniu i definiowaniu istoty Internetu przez różne kraje powodują znaczny potencjał konfliktów politycznych w skali globalnej. Prowadzi to autora do wniosku, że konieczne jest utworzenie instytucji zdolnych do zapobiegania konfliktom informacyjnym w przestrzeni internetowej i ich regulowania, a także do ograniczania globalnego ryzyka politycznego (w tym ryzyka związanego z potencjalną ingerencją w proces wyborczy suwerennych państw) i formowania zbiorowej odpowiedzialności za funkcjonowanie globalnego Internetu.
Interwencja cyfrowa w krajowych systemach politycznych w warunkach współczesnego społeczeństwa informacyjnego
Keywords: Internet communications; digital interference; informational confrontation; political system; electoral process; komunikacja internetowa; ingerencja cyfrowa; konfrontacja informacyjna; system polityczny; proces wyborczy